Redesign Website E-Learning Universitas Universal Dengan Pendekatan Design Thinking - Kelvin; Cantona, Erik (Fakultas Komputer - Universitas Universal, 2023)
The aim of this research is to maximize the use of e-learning applications by students for easier access to academic knowledge. The method used is Design Thinking. This method applies a solution-based approach that is used to solve problems, understand application users to define existing problems, then make solutions to solve existing problems. starting from looking for respondents to know the problems faced and followed by determining the problem and the results from the respondents will be processed and will become a new design that can solve user problems.